Comparison of diversity and community structure of aquatic insects based on habitat class in Johor - M. Z., Zakaria; M., Maryati (2021)
Aquatic insects had been well used as a tool in monitoring water quality and this study is aimed to gauge their potential in Johor. The rapid development in the state of Johor may cause pollution to water resources that require a more efficient water quality monitoring program. The objectives of this study were to (i) collect, identify, determine and produce aquatic insect diversity data in selected rivers in Johor, (ii) relate the presence of aquatic insect diversity with some of the physical features of rivers in Johor. Seven sampling areas were selected based on their importance to local communities and geographical distribution: Taman Negara Johor Endau Rompin (PETA) (TNJER-PETA), Taman Hutan Lagenda Gunung Ledang (THLGL), Hutan Lipur Soga Perdana (HLSP), Hutan Lipur Gunung Belumut (HLGB), Hutan Lipur Sungai Bantang (HLSB), Hutan Lipur Gunung Pulai 1 (HLGP1) and Sungai Sayong Pinang. Insect samples were collected using a kick net method and slight modifocation made according to type of microhabitats. A total of 11,647 individuals of aquatic insects consisting of 68 families from nine orders were sampled. About 69% of insects collected were indicators of good water quality; among them are families Hydropsychidae from order Trichoptera, Baetidae from Order Ephemeroptera, and Simuliidae from Order Diptera. Based on family diversity analyzed using Shannon Index (H’), TNJER- PETA is recorded having the highest index (H’= 3.215) followed by HLSP (H’= 2.791) and HLGB (H’= 2.482). Comparison made and based on physical characteristics, the study sites were classified into three categories (i) the most preferred sites by aquatic insects (HLSB, THLGL, HLGP1, and HLGB), (ii) intermediate preferred sites (TNJER-PETA and HLSP) and (iii) least preferred site (Sg. Sayong). In conclusion, community structure of benthic organisms were influenced by many factors such as presence of variety of microhabitat, predation, surrounding environments, food availability, physical and chemical characteristics of water. Moreover, higher heterogeneity of habitat promote high abundance and diversity of aquatic insects. Any changes happened that involves human interference in the habitats, will affect the abundance of aquatic insects. Last but not least, results suggested that the quality of river water in Johor can be monitored using insects as biological indicators due to the abundance, distribution, and rapid response of aquatic insects to environmental conditions.